Seleção de isolados de beauveria bassiana (Bals.) Vuill. para o controle de sitophilus zeamais (Mots.) (Coleoptera: Curculionidae) - Rondelli, Vando Miossi; de Carvalho, José Romário; Pratissoli, Dirceu; Polanczyk, Ricardo Antonio [UNESP]; de Alencar, João Rafael de Conte Carvalho [UNESP]; Zinger, Fernando Domingo; Pereira, Sara Maria Andrade (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2012)
Sitophilus zeamais (Mots.) (Coleoptera: Curculionidae) is considered a major pest of maize, responsible for reducing grain quality and making the corn inappropriate for industrial use and human consumption. S. zeamais has been controlled exclusively with chemical products. The objective of this research was to select isolates of Beauveria bassiana (Bals.) Vuill. to control S. zeamais. Beetles were immersed in conidia suspensions of each isolate for five seconds and placed in a gerbox container with maize grains. In pathogenicity tests, the isolates that caused the highest mortality to the maize weevil were ESALQ-447 (68.0%), CCA-UFES/ Bb-36 (57.3%) and CCA-UFES/Bb-31 (51.3%). ESALQ-447 was the most virulent, with an LC50 of 1.7 × 107 conidia/ml and shows promise for controlling maize weevils. These isolates of B. bassiana can be used as effective substitutes for conventional chemical control, normally carried out with phosphine. Further tests should be performed under field and semi-field conditions to develop an appropriate strategy for the use of this entomopathogen to manage S. zeamais.
Selection of beauveria bassiana (Bals.) Vuill. Isolates for controlling Sitophilus zeamais (Mots.) (Coleoptera: Curculionidae)
Keywords: Entomopathogenic fungus; Maize weevil; Microbial control; Stored grains